2015
DOI: 10.1093/pubmed/fdv042
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors associated with hospital-acquired pneumonia in an adult ICU: 4-year prospective cohort study in a university reference hospital

Abstract: Although severity of illness upon admission (APACHE II index) and decreased level of consciousness were relevant predisposing factors to contract HP in the ICU, the strongest association corresponded to extrinsic factors such as mechanical ventilation and use of a nasogastric tube. The fact that these are therapeutic interventions facilitates developing prevention and control measures that can contribute to reduce the risk for HP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 15 publications
4
17
2
5
Order By: Relevance
“…Mechanical ventilation has been confirmed as an independent risk factor of nosocomial pneumonia because artificial airways are a serious risk factor for micro-aspirations [36]. This was the largest contributing factor for nosocomial infection in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Mechanical ventilation has been confirmed as an independent risk factor of nosocomial pneumonia because artificial airways are a serious risk factor for micro-aspirations [36]. This was the largest contributing factor for nosocomial infection in our study.…”
Section: Discussionsupporting
confidence: 66%
“…Compared with the Note: -, not detected severe group, the critical group had a signi cantly increased mortality. Recent studies related to COVID-19 reported that male was a risk factor for disease severity status, and age 65 or older was a risk factor related to death [3,17,18]. In our research, no differences in gender and age were found between the severe and critical groups.…”
Section: Discussioncontrasting
confidence: 52%
“…By contrast, the presence of an inserted GT is considered as a significant risk factor, as seen from a recent large study of 4427 patients documenting that mechanical ventilation and the use of a GT were the most significant risk factors for the development of HAP (ref. 17 ). Apart from the insertion of a GT, patient immobility is a stronger risk factor for HAP than dysphagia, as shown by Brogan et al 18 .…”
Section: Discussionmentioning
confidence: 99%